Acid-assisted synthesis of TiO2 nanoparticles for enhancement of visible light photocatalytic efficiency. Issue 3 (April 2021) - Gu, Yi-Jie; Zhou, Ming; Dong, Zhihua; Cheng, Zhiqun; Deng, Tian-Song
Abstract: Compared with pure phase TiO2, the mixed-phase TiO2 nanoparticles with oxygen vacancies can help to reduce the carrier recombination rate and band gap, which is contribute to the visible light photocatalysis performance. In this study, three kinds of acid were separately used to prepare TiO2 nanoparticles by hydrothermal method without any post-heat treatment for enhancement of visible light photocatalytic efficiency. When utilized to assist photocatalysis degradation of methyl orange in water under visible light irradiation, the TiO2 nanoparticles obtained from HCl (H-TiO2 ) and CH3 COOH (A-TiO2 ) showed stable photocatalysis performance for increasing the cycles up to ten times while only five cycles for TiO2 nanoparticles obtained by HNO3 -assisted (N-TiO2 ). The photocatalysis performance of H-TiO2 powder and A-TiO2 powder are both better than that of the N-TiO2 powder. Therefore, the TiO2 samples prepared by HCl- and CH3 COOH-assisted method in this work are regarded as excellent photocatalysts for water cleaning.